Refining the resolution of craniofacial dysmorphology in bipolar disorder as an index of brain dysmorphogenesis - Katina, Stanislav; Kelly, Brendan D; Rojas, Mario A; Sukno, Federico M; McDermott, Aoibhinn; Hennessy, Robin J; Lane, Abbie; Whelan, Paul F; Bowman, Adrian W; Waddington, John L (Psychiatry research, 2020)
As understanding of the genetics of bipolar disorder increases, controversy endures regarding whether the origins of this illness include early maldevelopment. Clarification would be facilitated by a 'hard' biological index of fetal developmental abnormality, among which craniofacial dysmorphology bears the closest embryological relationship to brain dysmorphogenesis. Therefore, 3D laser surface imaging was used to capture the facial surface of 21 patients with bipolar disorder and 45 control subjects; 21 patients with schizophrenia were also studied. Surface images were subjected to geometric morphometric analysis in non-affine space for more incisive resolution of subtle, localised dysmorphologies that might distinguish patients from controls. Complex and more biologically informative, non-linear changes distinguished bipolar patients from control subjects. On a background of minor dysmorphology of the upper face, maxilla, midface and periorbital regions, bipolar disorder was characterised primarily by the following dysmorphologies: (a) retrusion and shortening of the premaxilla, nose, philtrum, lips and mouth (the frontonasal prominences), with (b) some protrusion and widening of the mandible-chin. The topography of facial dysmorphology in bipolar disorder indicates disruption to early development in the frontonasal process and, on embryological grounds, cerebral dysmorphogenesis in the forebrain, most likely between the 10th and 15th week of fetal life.
Keywords: Young Adult; zobrazování trojrozměrné; bipolární porucha; Male; mladý dospělý; Brain; Neurodevelopment; Schizophrenia; Adult; dospělí; mužské pohlaví; Imaging, Three-Dimensional; analýza hlavních komponent; obličej; Brain dysmorphogenesis; Principal Component Analysis; Craniofacial dysmorphology; lidé; ženské pohlaví; Humans; schizofrenie; Bipolar disorder; mozek; Face; Female; kraniofaciální abnormality; Geometric morphometrics; Craniofacial Abnormalities; Bipolar Disorder